miR-182 and miR-183 Promote Cell Proliferation and Invasion by Targeting FOXO1 in Mesothelioma - Suzuki, Rui; Amatya, Vishwa Jeet; Kushitani, Kei; Kai, Yuichiro; Kambara, Takahiro; Takeshima, Yukio (Frontiers in Oncology, 2018)
Dysregulation of miR-182 and miR-183 has been implicated in the progression of several human cancers. Our previous study showed that miR-182 and miR-183 are upregulated in malignant mesothelioma. However, their biological functions remain unclear. We performed in-situ hybridization to analyze the expression of miR-182 and miR-183 in human tissues. Functional analysis was performed by treatment of two mesothelioma cell lines (ACC-MESO1 and CRL-5915) with miR-182 and miR-183 inhibitors. RT-PCR and western blot analysis were conducted to analyze the expression of FOXO1, a known target of both miR-182 and miR-183. Mesothelioma cells treated with FOXO1 siRNA and miR-182/183 inhibitors were also analyzed by evaluating cell proliferation and invasion, as well as expression of FOXO1 and its downstream targets. We confirmed miR-182 expression in 25/29 cases and miR-183 expression in 29/29 cases of human mesothelioma tissue by in-situ hybridization. Notably, inhibition of miR-182 or miR-183 reduced cell proliferation, invasion, migration, and adhesion abilities of mesothelioma cells. Surprisingly, transfection with both miR-182 and miR-183 inhibitors showed even more effects on cell progression. Furthermore, FOXO1 was identified as a target of miR-182 and miR-183 in mesothelioma cells. Inhibition of miR-182 and miR-183 reduced cell proliferation ability via upregulation of FOXO1 and its downstream targets, namely, p21 and p27. Moreover, inhibition of miR-182 and miR-183 reduced the cell invasion properties of mesothelioma cells. Our findings indicated that miR-182 and miR-183 promote mesothelioma cell progression via downregulation of FOXO1 and p21/p27. Targeting the miR-182/183 - FOXO1 axis could serve as a novel treatment against malignant mesothelioma.